2022
DOI: 10.1016/j.sleep.2021.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia symptoms during the early and late stages of the COVID-19 pandemic in China: a systematic review and meta-analysis

Abstract: Background Evidence suggests that the outbreak of the coronavirus disease 2019 (COVID-19) and the prevention/control measures for COVID-19 may cause insomnia during the acute phase of COVID-19 pandemic in China. However, it is unclear whether insomnia sustains during the later phases of the pandemic. Methods We searched PubMed/Medline, EMBASE, PsycINFO and China National Knowledge Infrastructure from the 27 th December 2019 to the 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 57 publications
3
32
0
1
Order By: Relevance
“…The inconsistency in the prevalence of "depression" may be caused by the regional disparity, given that the pandemic of COVID-19 in the USA was serious and healthcare workers there suffered more workload. However, many studies reported a higher prevalence of "insomnia" among healthcare workers than the general population 48,[50][51][52][53] , in accord with our result. In addition, compared with the general population, healthcare workers focused more on discussing the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus and preferred to share COVID-related news or experiences.…”
Section: Discussionsupporting
confidence: 92%
“…The inconsistency in the prevalence of "depression" may be caused by the regional disparity, given that the pandemic of COVID-19 in the USA was serious and healthcare workers there suffered more workload. However, many studies reported a higher prevalence of "insomnia" among healthcare workers than the general population 48,[50][51][52][53] , in accord with our result. In addition, compared with the general population, healthcare workers focused more on discussing the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus and preferred to share COVID-related news or experiences.…”
Section: Discussionsupporting
confidence: 92%
“…A recent meta-analysis reported pooled prevalence of de insomnia of the global population was 23.87% [ 10 ]. Evidence from China, compared with a pooled prevalence estimate of insomnia (315%) absent of pandemic [ 11 ], pooled prevalence from a recent meta-analysis conducted during the COVID-19 was more than two times higher (39.1%) [ 12 ], which to a certain extent reflects a significant impact of the COVID-19 pandemic on sleep. Meanwhile, younger people are more vulnerable to stress during COVID-19 pandemic [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high incidence of insomnia reported by Schou et al (2021) and Huang et al (2021) was confirmed by Li et al (2021b). Their report documented about 37% of patients with COVID-19 had insomnia in the early stage which rose to 41.8% in the later stage.…”
Section: Long Covid Psychiatric Disordersmentioning
confidence: 82%